2022
DOI: 10.1021/acs.chemrev.1c00935
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of High-Nitrogen Materials and Energetic Materials

Abstract: Electrochemical synthesis is a valuable method for the preparation of molecules. It is innately eco-friendly, as potentially hazardous oxidation and reduction agents are replaced with electrochemical potentials. Electrochemistry is commonly applied globally in the synthesis of numerous chemicals, but the energetic materials field lags in this regard. In this review, we endeavor to cover the entire history of synthetic electrochemistry for the preparation of energetic materials and detail the electrochemical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 179 publications
0
38
0
Order By: Relevance
“…[14,23] However, only a few OEMs have been successfully obtained by facile electrochemical pathways; thus, OEM electrosynthesis lags behind the global electrochemical synthesis of numerous chemicals. [24] Yount et al demonstrated the successful electrooxidation of 3,4,5-triamino-1,2,4-triazole and yielded new OEMs with superior thermal stability and low sensitivity toward impact and friction. [14] Sheremetev et al reported the electrooxidation of aminofurazans to azofurazans on a nickel oxyhydroxide anode.…”
Section: Introductionmentioning
confidence: 99%
“…[14,23] However, only a few OEMs have been successfully obtained by facile electrochemical pathways; thus, OEM electrosynthesis lags behind the global electrochemical synthesis of numerous chemicals. [24] Yount et al demonstrated the successful electrooxidation of 3,4,5-triamino-1,2,4-triazole and yielded new OEMs with superior thermal stability and low sensitivity toward impact and friction. [14] Sheremetev et al reported the electrooxidation of aminofurazans to azofurazans on a nickel oxyhydroxide anode.…”
Section: Introductionmentioning
confidence: 99%
“…In the latest decades, owing to unique chemical properties and environmental friendliness, green nitrogen-rich insensitive high-energy density materials (HEDMs) for military and civilian applications have gained widespread research attention in the area of energetic materials. As a unique class of novel HEDMs, fused cyclic energetic materials have been recognized as promising alternatives to conventional energetic materials. , Benefiting from considerably high heats of formation (HOF) and ring-strain energy, the fused-ring energetic compounds with a coplanar polycyclic structure usually show high detonation properties, improved thermostability, and significant insensitivity against external mechanical stimuli, which greatly increases the safety of the production, handling, transfer, and storage of new materials. However, the limited number of fused-ring frameworks available for the preparation of various molecules has severely hindered their further expansion in energetic materials chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, explosive growth of high-energy-density materials based on derivatives of five- or six-membered azines has occurred. Energetic metal–organic frameworks (EMOFs) assembled from metallic nodes with nitrogen-rich azines have gained much interest because of their dense crystalline structures. The preparation of EMOFs has undergone substantial advancement, from one-dimensional (1D) and two-dimensional (2D) EMOFs to the emergence of three-dimensional (3D) EMOFs. Moreover, these 3D energetic frameworks possess more complex linking modes in comparison with 1D linear and 2D layered structures, which improves their structural reinforcement and molecular stabilities. Nowadays, these 3D EMOFs play a central role in modern energetics because of their prevalent occurrence across a broad range of applications such as explosives, oxidizers, and pyrotechnics. , New EMOFs should preferably have good detonation properties, high density, and good thermal stability, along with ease of synthesis, high atom economy, and waste prevention. Therefore, tuning the structures and physicochemical properties of existing energetic structures by tailoring their properties for required applications is highly desirable …”
Section: Introductionmentioning
confidence: 99%